Improving the quality of Napier grass silage with pyroligneous acid: Fermentation, aerobic stability, and microbial communities - Chen, Dandan; Zheng, Mingyang; Zhou, Yuxin; Gao, Lin; Zhou, Wei; Wang, Mingya; Zhu, Yongwen; Xu, Weijie (Frontiers in Microbiology, 2022)
Undesirable microorganisms always lead to poor fermentation quality and low aerobic stability of silage. Pyroligneous acid (PA), a by-product of biochar production, is known to have strong antimicrobial and antioxidant activities. To investigate the effects of PA on fermentation characteristics, aerobic stability, and microbial communities, napier grass was ensiled with or without 1% and 2% PA for 30 days and then aerobically stored for 5 days. The results showed that PA application decreased (P < 0.01) pH value, ammonia nitrogen content, and the numbers of undesirable microorganisms (coliform bacteria, yeasts and molds) after 30 days ensiling and 5 days exposure to air. The temperature of PA-treated groups was stable during 5-day aerobic test, which did not exceed room temperature by 2℃. The addition of PA also enhanced the relative abundance of Lactobacillus and reduced that of Klebsiella, and Kosakonia. The relative abundance of Candida was higher in PA treated silages, compared to the untreated silage. The addition of PA decreased the relative abundance of Kodamaea and increased that of Monascus after 5 days exposure to air. The abundances of Cladosporium and Neurospora were relatively high in 2% PA treated NG, while these genera were invisible in the control group. The above results suggested that the addition of PA could improve fermentation characteristics and aerobic stability, as well as alter microbial communities of silage.